THE CONCEPT OF ISLAMIC EDUCATION CURRICULUM: A STUDY OF IBN SINA'S THOUGHT - Azizah, Hesty Hyldania (Abjadia : International Journal of Education, 2024)
This study aims to provide an analysis of the concept of Islamic education curriculum according to Ibn Sina's perspective. Ibn Sina is a Muslim scholar who is famous for his intelligence. Even his intelligence exceeded the ability of scholars at that time. According to Ibnu Sina, the basic Islamic education is Al-Quran education which starts as early as possible, after that they are introduced to letters and poetry about politeness. In addition, according to Ibnu Sina, the purpose of education is to help students prepare themselves to live in society and get jobs according to their interests and talents. This study uses a literature review approach or library research by analyzing various literature studies related to Ibn Sina's perspective on Islamic education. The findings obtained are that Ibn Sina conceptualized Islamic education by first teaching Al-Quran education. In addition, everything that has been conceptualized by Ibn Sina is still very relevant to Islamic education today starting from curriculum concepts, students, educators, learning methods, and punishments in education.